2007
DOI: 10.1111/j.1440-1681.2007.04636.x
|View full text |Cite
|
Sign up to set email alerts
|

Narirutin Inhibits Airway Inflammation in an Allergic Mouse Model

Abstract: 1. Flavonoids are naturally occurring compounds that possess anti-allergic, anti-inflammatory, antiproliferative and anti-oxidant properties. In the present study, we investigated whether the flavonoid narirutin could reduce airway inflammation in ovalbumin (OVA)-sensitized/challenged NC/Nga mice, a model of allergic eosinophilic airway inflammation. 2. Mice were initially immunized intraperitoneally with OVA on Days 0 and 7 and then challenged with inhaled OVA on Days 14, 15 and 16. In addition, some mice rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…Thinking about the abundance ratio of flavonoids, narirutin is considered to contribute to antiinflam matory effect at oral ingestion of C. jabara fruit peels. Funaguchi et al also reported that oral administration of narirutin inhibited airway inflammation in allergic model mouse [25] . On the other hand, in vitro cell assay, narirutin did not exhibited enough anti-inflammatory effects (Figures 2-5) nor anti-degranulating effects [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Thinking about the abundance ratio of flavonoids, narirutin is considered to contribute to antiinflam matory effect at oral ingestion of C. jabara fruit peels. Funaguchi et al also reported that oral administration of narirutin inhibited airway inflammation in allergic model mouse [25] . On the other hand, in vitro cell assay, narirutin did not exhibited enough anti-inflammatory effects (Figures 2-5) nor anti-degranulating effects [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an epidemiologic study found that a higher intake of flavonoids was associated with a lower incidence of asthma [44]. In experimental models, oral administration of flavonoids has been demonstrated to prevent allergic diseases including asthma, anaphylaxis, food allergies and atopic dermatitis [16, 17,32,33,34,35,36,37]. This study showed that the ocular symptoms were reduced in the EMIQ group.…”
Section: Discussionmentioning
confidence: 69%
“…We and others have shown that some kinds of flavonoids including apigenin, fisetin, luteolin and quercetin suppress the expression of Th2-type (IL-4, IL-5 and IL-13) [13, 14], proinflammatory cytokines [31] and CD40 ligand [15] in basophils or in mast cells. In addition to these in vitro antiallergic activities, studies with allergic animal models have demonstrated that flavonoids exert preventative and therapeutic effects by modifying Th2-type cytokine expression and suppressing IgE elevation [16, 17,32,33,34,35,36,37]. In our study we measured the serum levels of cytokines and chemokines before and after the study but found no significant reduction in Th2 cytokines (IL-4, IL-5 and IL-13), chemokines (eotaxin) or IgE concentration as a result of EMIQ intake except for TARC (fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that nobiletin, a polymethoxyflavonoid, when given intraperitoneally to OVA-sensitized rats at a dose of 1.5 or 5 mg/kg, reduced OVA-induced increases in eosinophils and eotaxin expression (Wu et al, 2006). In subsequent investigations, flavonoids such as quercetin, isoquercitrin, rutin, 3-O-methylquercetin 5,7,3',4'-O-tetraacetate, narirutin, apigenin, luteolin, sulfuretin, hesperdin, fisetin and kaempferol have been shown to suppress responses in various types of allergic animals (Makino et al, 2001;Fernandez et al, 2005;Rogerio et al, 2007;Jung et al, 2007;Jiang et al, 2007;Funaguchi et al, 2007;Yano et al, 2007;Cruz et al, 2008;Choi et al, 2009;Li et al, 2010;Leemans et al, 2010;Shishebor et al, 2010;Kim et al, 2011;Wu et al, 2011;Gong et al, 2012).…”
Section: Efficacy Of Flavonoids In Allergic Modelsmentioning
confidence: 99%